Student’s concept ability of Newton’s law based on verbal and visual test - N. D. Setyani; Cari Cari; Suparmi Suparmi; J. Handhika (Universitas Sebelas Maret, 2017)
Newton’s law is a foundamental concept that needs to be studied and understood correctly. Concept presentation in different representation will help the student to understand the concept that being learned. Student’s ability to present Newton’s law in different representation indicate the quality of student’s concept ability. This research aims to describe student’s concept ability of Newton’s laws based on the student’s ability of verbal and visual (pictorial and graphical) problem solving. The method of this research is qualitative with the sample of 71 students of physics education from IKIP PGRI Madiun (14 students) and Sebelas Maret University (57 students). The instrument used in this research were conceptual test and interview. The result showed that more student provide incorrect answer to the physics conceptual problem. Percentage of the incorrect answer for First Newton’s law problem is 69 %, Second Newton’s law problem is 71 %, and Third Newton’s law problem is 76 %. The students do not understand the language of physics correctly, they undergo incorrect physics concept, and so they only understand few physics concept of Newton’s law.